Application of the RADEC Learning Model in Enhancing Students' Critical Thinking Skills in Social Studies Learning - Anwar Anwar; Aminah Lubis; Delisma Siregar; Eka Nurbulan; Emi Juwita Saragi; Sugiharto Sugiharto; Syarifah Syarifah (EDUTEC : Journal of Education And Technology, 2024)
The objective of this research is to examine the implementation of the RADEC (Read, Answer, Discuss, Explain, and Create) learning model in enhancing students' critical thinking skills in social studies. A descriptive analysis was conducted to compare the pretest and posttest results between the experimental and control groups, focusing on students' critical thinking abilities. The data presented in Table 1 show that in the experimental group, the pretest score was 50.87 and the posttest score was 87.13, resulting in a difference of 36.26. In the control group, the pretest score was 50.20 and the posttest score was 85.73, yielding a difference of 35.53. These results indicate a significant improvement in the average critical thinking skills of students in both groups, with a slightly higher increase observed in the experimental group. Therefore, it can be concluded that the application of the RADEC model is effective in improving students' critical thinking skills in social studies.